Relação entre valores de pressão arterial obtidos pela M.A.P.A e o desenvolvimento de lesões em órgãos-alvos nos hipertensos atendidos em ambulatório público de atenção terciária - Landim, Manoel Ildefonso Paz (2017)
The causal relationship between hypertension and the development of target organ damage (TOD) is very well established, but the contribution of absolute blood pressure values to the genesis of TOD has been questioned. This study makes a comparative analysis between the values of Blood Pressure and the triggering of Target Organ Lesions in a hypertensive population, in order to verify the possibility of a dependence between high blood pressure figures and the appearance of lesions. Objective - To relate blood pressure levels obtained by ABPM with the appearance of LVH, stroke, CAD and microalbuminuria in a selected population of hypertensive patients. Casuistic and Methods: One hundred and sixty two patients belonging to the FAMERP hypertension outpatient clinic who met the inclusion criteria were studied, and the occurrence of the outcomes was considered. The minimum period of follow-up was five years and the maximum period was fifteen years. At the end of the data collection, statistical analyzes were sufficient to answer if higher values of arterial pressure were related, or not, to greater number of TOD. We also sought to confirm existence of other related variables, which could contribute positively or negatively to the appearance of the outcomes. Results: Only the increase in left ventricular mass and the occurrence of CAD are significantly related to the abnormal behavior of the arterial pressure and, even then, only to the nocturnal mean higher than the reference for mass increase and the diastolic mean of 24 hour ABPM recorded at the end of the observation period for the CAD. The appearance of outcomes, objective of this study is significantly more related to metabolic factors, comorbidities and/or to epidemiological parameters than to the increase in numerical values of blood pressure. The appearance of microalbuminuria in the multivariate analysis was positively related to DMII (p= 0.0029) and TG (p= 0.003). The same can be observed for stroke (male gender with p= 0.009; HDL= 0.016; PAD= 0.003; microalbuminuria p= 0.003 and LVH at the end of the observation p= 0.029). Diabetes mellitus II was also protagonist in the evolution for LVH, with p= 0.030 in the univariate analysis and p= 0.037 when there was multivariate refining. When studying the onset of CAD, besides the pressure component, we have also recorded age older than or equal to 65 years (p= 0.019 in the univariate comparison and p= 0.002 in the multivariate), HDL-c (p= 0.009 in the univariate and p= 0.004 in the multivariate) and PAD (p= 0.047). Conclusions: Increases in blood pressure levels lato sensu were not accompanied by a corresponding increase in the number of CAD, LVH, stroke or microalbuminuria in the studied population, except non dipper